TRANSPORTATION AND MOBILITY TECHNOLOGY FUTURES intelligent systems, decarbonization and... micromobility. - LEE, SUNGWON (ROUTLEDGE, 2026)
Emerging technologies in the transport sector have had, and will have, profound implications for the betterment of our daily lives and economic prosperity. This book delves into modern and emerging transportation technologies, highlighting their significance as they transform how we move people and goods, offering crucial insights for navigating the future of transportation systems. It also discusses policy implications of these technologies, and touches on economic and econometric methodologies for analyzing transportation policy impacts.Emerging transport technologies, such as autonomous vehicles, ITS, and V2X, along with new trends relating to how we use transport services, will shape our daily mobility, and related industries will flourish. This book discusses the recent trends in technology development for mobility and deals with important related issues such as technology acceptance and related policies. Recognizing the importance of the topic, the book provides a comprehensive review of emerging technology developments and their prospects. It also serves as an analytical framework for assessing their impacts and discusses related issues such as people's reactions and legal frameworks that may be required.This book is written primarily for transport professionals in government or consulting, but it is also appropriate for academic use, or for anyone with an interest in transportation and cities.
Keywords: Transportation -- Technological innovations.; elektronické knihy; electronic books